2022
DOI: 10.2334/josnusd.21-0217
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and factors associated with maxillary sinus cyst in a Chinese population

Abstract: Purpose: This study used cone-beam computed tomography (CBCT) to assess the prevalence of and factors associated with maxillary sinus cysts (MSCs) in a Chinese population. Methods: A total of 2,571 CBCT scans of 5,000 sinuses were analyzed. MSCs were diagnosed on the basis of imaging features within the maxillary sinus. Sex, age, dental condition, and anatomic condition were assessed. Associations with these factors were evaluated with logistic regression and a generalized estimating equations model. Results:T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…MRCs are commonly found in the maxillary sinus ( Figure 5 ). MRCs were found in 10.1– 28.6% of the maxillary sinus [ 28 , 75 , 76 , 77 ]. Up to four MRCs were reported within a single sinus [ 75 , 77 ].…”
Section: Pathologymentioning
confidence: 99%
See 3 more Smart Citations
“…MRCs are commonly found in the maxillary sinus ( Figure 5 ). MRCs were found in 10.1– 28.6% of the maxillary sinus [ 28 , 75 , 76 , 77 ]. Up to four MRCs were reported within a single sinus [ 75 , 77 ].…”
Section: Pathologymentioning
confidence: 99%
“…MRCs were found in 10.1– 28.6% of the maxillary sinus [ 28 , 75 , 76 , 77 ]. Up to four MRCs were reported within a single sinus [ 75 , 77 ]. MRCs were more commonly located at the sinus walls (19.9–53.6%) and the floor (28.6–76.7%) instead of the roof (3.4–17.9%) [ 75 , 77 ].…”
Section: Pathologymentioning
confidence: 99%
See 2 more Smart Citations
“…With a prevalence of 15.46% at the sinus level and 23.44% at the patient level (Ren et al, 2022), maxillary sinus cysts are commonly observed in Chinese dental implant patients. Maxillary sinus pseudocysts, also known as antral pseudocysts (APs), are asymptomatic, solitary or multiple maxillary sinus “cysts” (Carter et al, 1998; Gardner, 1984; Nosaka et al, 2021).…”
Section: Introductionmentioning
confidence: 99%